Development as Process: Concepts and Methods for Working with Complexi ty - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be mo re flexible and offer greater prospects of success than traditional "p roject" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine d evelopment projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-ag ency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources de velopment in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Keywords: Demography; Economic Development; Sociology